Perspectives on Effects of Teacher Turnover on Students’ Academic Performance in Secondary Schools In - Orwa, Beatrice Akinyi; Ajowi, Jack; Okwara, Michael (Published by European Centre for Research Training and Development UK, 2017)
Teacher turnover poses a threat to the education sector by limiting or reducing the availability of qualified teachers to undertake teaching services. The purpose of this study was to assess the effects of teacher turnover on students’ academic performance from the perspectives of head-teachers, teachers and students in secondary schools in Gem Sub-County, Siaya County. The research design was a descriptive survey research design. The study estimated the effects of teacher turnover in 14 secondary schools out of 42 secondary schools in Gem sub-county. This involved 14 head-teachers, 163 teachers and 371 students. To obtain the sample of the study, stratified random sampling was used. Data was collected using questionnaires document analysis guide and interviews. The data was analyzed using frequency distribution tables, measures of central tendency and percentages. The main factors of turnover reported in the study were resignation for non-teaching jobs or further studies, poor working conditions, poor transport system, social security, poor medical services, maternity commitments and school policies. The main effects of turnover reported were teacher shortage, poor syllabus coverage, impact on student’s academic performance, disruption of teaching, learning and school planning, increased workload and reputation of the school. It is therefore necessary that controlling agencies should address themselves about this turnover and restore to schools the quality and dignity intended for them. This calls for an adoption of programmes geared towards the achievement of objectives, standardization of entry behaviours and discipline on the job.
Keywords: Teacher Turnover; Performance; Planning; Workload; Perspectives